Answer:
see explanation
Explanation:
Given
2y² - 7y - 4 = 0 ← in standard form
(2y + 1)(y - 4) = 0 ← in factored form
Equate each factor to zero and solve for y
2y + 1 = 0 ⇒ 2y = - 1 ⇒ y = -
![(1)/(2)](https://img.qammunity.org/2021/formulas/physics/middle-school/ukxexrkoplrwscaxd96qbbkphc5fo6w2ur.png)
y - 4 = 0 ⇒ y = 4
(b)
Comparing this equation to the one given in (a) , then
= y
Using the solutions from part (a)
= -
( multiply both sides by - 1 )
-
=
[ note that
=
]
x = - 1
= 4 [ note that 2² = 4 ]
x = 2